2019
DOI: 10.1021/acs.inorgchem.9b02534
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt(II)-Based 3D Coordination Polymer with Unusual 4,4,4-Connected Topology as a Dual-Responsive Fluorescent Chemosensor for Acetylacetone and Cr2O72–

Abstract: A cobalt­(II) coordination polymer with an unusual 4,4,4-connected network was hydrothermally synthesized and observed with high thermal, solvent, and pH stabilities. This polymer can serve as the first dual-responsive fluorescent chemosensor for the selective detection of acetylacetone and Cr2O7 2– ion (pH 3.0) in aqueous systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 175 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Many elements, for instance, metal ions and anti‐ions, solvent systems, and organic ligands, have a great effect on the molecular structures, which makes the construction of the molecular structures hard to predict. [ 13–16 ] Among them, the selection of the ligands is a pivotal factor. The relative positions, functional groups, and donor atoms can directly change the skeleton structures.…”
Section: Introductionmentioning
confidence: 99%
“…Many elements, for instance, metal ions and anti‐ions, solvent systems, and organic ligands, have a great effect on the molecular structures, which makes the construction of the molecular structures hard to predict. [ 13–16 ] Among them, the selection of the ligands is a pivotal factor. The relative positions, functional groups, and donor atoms can directly change the skeleton structures.…”
Section: Introductionmentioning
confidence: 99%
“…In general, if the lowest unoccupied molecular orbital (LUMO) of the electron‐rich frame holds a higher energy level than that of the analyte, then there is a probability of electron transfer. The results showed that the LUMO level of H 3 L ligand (−1.96 eV, Figure 8) is higher than that of acac (−2.36 eV), [32] confirming the existence of electron transfer, which reduces the fluorescence of MOF 1 , (iv) Theoretically, acac molecule should be a potential candidate for hydrogen‐bonded synthon due to keto‐enol tautomerism. It is estimated that there might be H‐bond interaction between the −OH moiety of the enol form of acac and the uncoordinated oxygen atom of H 3 L ligand.…”
Section: Characterizationmentioning
confidence: 79%
“…The K sv and detection limit values for LCP 1 are comparable to those of the CPs reported in the literature (Tables S4 and S5 †). 10,[27][28][29][30][31][32] The sensing selectivity of LCP 1 for Hacac or NB in the presence of other interferential analytes (including DMF, ProOH, DMA, PhH, THF, Py, EtOH, CyH, MeOH, ACN, iso-ProOH, EG, DCM, 1,4-dioxane, and DMSO) were evaluated. First, equal amount of interferents were mixed to form a mixture.…”
Section: Sensing Of Organic Solventsmentioning
confidence: 99%